KAJIAN POPULASI KEPITING KENARI DI PULAU BATUDAKA KEPULAUAN TOGEAN, SULAWESI TENGAH DAN REKOMENDASI MANAJEMEN POPULASI - Heryanto, Heryanto; Wowor, Daisy (Perhimpunan Biologi Indonesia, 2017)
ABSTRACTThis study aimed to quantify the population of Birgus latro in the Batudaka di Togean islands, Central Sulawesi. The research on robber crab was conducted in Batudaka Island, Togean, Tomini Bay, Central Sulawesi. In the study site, 21 plots measuring of 50x50 m2 were created bounded by raffia. Feed in the form of shredded coconut is placed in each plot in the afternoon. At night was performed observations and catchs. In the